The Redox Balance and Membrane Shedding in RBC Production, Maturation, and Senescence - Fibach, Eitan (Frontiers in Physiology, 2021)
Membrane shedding in the form of extracellular vesicles plays a key role in normal physiology and pathology. Partial disturbance of the membrane-cytoskeleton linkage and increased in the intracellular Ca content are considered to be mechanisms underlying the process, but it is questionable whether they constitute the primary initiating steps. Homeostasis of the redox system, which depends on the equilibrium between oxidants and antioxidants, is crucial for many cellular processes. Excess oxidative power results in oxidative stress, which affects many cellular components, including the membrane. Accumulating evidence suggests that oxidative stress indirectly affects membrane shedding most probably by affecting the membrane-cytoskeleton and the Ca content. In red blood cells (RBCs), changes in both the redox system and membrane shedding occur throughout their life – from birth – their production in the bone marrow, to death - aging in the peripheral blood and removal by macrophages in sites of the reticuloendothelial system. Both oxidative stress and membrane shedding are disturbed in diseases affecting the RBC, such as the hereditary and acquired hemolytic anemias (i.e., thalassemia, sickle cell anemia, and autoimmune hemolytic anemia). Herein, I review some data-based and hypothetical possibilities that await experimental confirmation regarding some aspects of the interaction between the redox system and membrane shedding, and its role in the normal physiology and pathology of RBCs.